2021
DOI: 10.1136/bmjspcare-2020-002713
|View full text |Cite
|
Sign up to set email alerts
|

From COVID-19 adversity comes opportunity: teaching an online integrative medicine course

Abstract: BackgroundWe examine the impact of a 5-day online elective course in integrative medicine (IM) taking place during the COVID-19 pandemic, attended by 18 medical students from two faculties of medicine in Israel.MethodsThe course curriculum addressed effectiveness and safety of IM practices highlighting supportive and palliative care, demonstrated the work of integrative physicians (IPs) in designing patient-tailored treatments and taught practical skills in communication regarding IM. Group discussions were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Gibbins showed that e-learning for medical students changes attitudes on "palliative thinking" [11]. Until now, many studies have only involved medical students in research questioning the use of e-learning in PC [11][12][13][14][15]. A mixed-methods study asking all PC health care workers in Ireland to name factors that motivate participation in e-learning revealed the following responses: dedicated time to participate in e-learning activities, quick technical and administrative support, computer training before completing an e-learning course, and regular contact with the tutor in online course work [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gibbins showed that e-learning for medical students changes attitudes on "palliative thinking" [11]. Until now, many studies have only involved medical students in research questioning the use of e-learning in PC [11][12][13][14][15]. A mixed-methods study asking all PC health care workers in Ireland to name factors that motivate participation in e-learning revealed the following responses: dedicated time to participate in e-learning activities, quick technical and administrative support, computer training before completing an e-learning course, and regular contact with the tutor in online course work [8].…”
Section: Introductionmentioning
confidence: 99%